Right to work break or lunch break? Comments on the preliminary project of the Labor Code - Huamán Ordóñez, Luis Alberto (2022)
The author of this essay analyzes the right to lunch break based on the approach made through the preliminary project of the Labor Code proposed by the Executive Branch, and focuses on developing the scope of the right to a work break as a stand-alone definition of lunch break since it refers not only to consuming food, especially to having lunch, but to developing a space for personal interaction that allows employees to continue with their work activities after the time given by employers for food consumption. While it is recognized that the right to work break does not have a direct constitutional reference, it is worth noting that it comes from the sum of the fundamental rights to dignity and health. In accordance with what is argued, this analysis specifies the need for the right to work break to be valued more broadly, and we should focus on developing the bases by which it should be considered as a working condition in the preliminary project of the Labor Code.